Acute response to training after returning from the off-season in elite rugby league athletes - Simmons, R. G.; Leicht, A.; Sinclair, W. H.; Bowman, P.; Dobbin, M.; Doma, K. (Journal of Human Kinetics, 2024)
The purposes of this study were to quantify the physiological response to the initial two-week preseason period in elite male rugby league (RL) athletes, and to determine if a repeated bout effect (RBE) occurs. Eighteen RL players were monitored for the initial two-week preseason period. Blood samples were collected on days (D)1, D2, D4, D5, D8, D9, D11 and D12 to measure creatine kinase (CK). Neuromuscular power was assessed on D1, D5, D8 and D12. During field-based sessions, the external training load was quantified using global positioning system technology, whilst the internal load was quantified using the training impulse and the session rating of perceived exertion. Resistance-based gym session volume was quantified by total repetitions x weight lifted. Perceived measures of fatigue and muscle soreness were assessed on all training days. Two-way (day x week) repeated measures analysis of variance and Bonferroni`s corrected post-hoc tests identified significant changes. There were no significant changes in CK activity (649.2 ± 255.0 vs. 673.8 ± 299.1 µL; p = 0.63) or internal training load measures from week 1 to week 2. External training load measures including total distance (4138.1 ± 198.4 vs. 4525.0 ± 169.2 m; p < 0.001) and repeated high-intensity efforts (12.6 ± 1.8 vs. 17.5 ± 1.8 au; p < 0.001) significantly increased in week 2 compared to week 1. Internal training loads and CK activity did not change in response to an increase in external training loads during the initial preseason. The current results provide support for a `real world` perspective of the RBE phenomenon that may be more applicable for team sport practitioners.